1899 Wyo. Rev. Stat. 1253, div. 5, tit. 1, ch. 3, § 5051 - (:unkn) unknown (General Publisher, 1899)
Every person, not being a traveler, who shall wear or carry any dirk, pistol, bowie knife, dagger, sword-in-cane, or any other dangerous or deadly weapon concealed, or who shall carry or wear any such weapon openly, with the intent, or avowed purpose, of injuring his fellow- man, shall be fined not more than one hundred dollars.
--
Keywords: CARRY - INTENT TO COMMIT CRIME